2012
DOI: 10.4103/1119-3077.97305
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss: Are the patients prepared?

Abstract: We observed that emotional effects of tooth loss are also experienced among our patients with a range of emotions quite similar to those observed by previous authors from the developed world. The significant number of patients that failed to come to terms with their tooth loss indicates that the effect of tooth loss on self-esteem and self-image is not short lived as it has been assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
2
10
0
9
Order By: Relevance
“…It can reduce the level of confidence that leads to people withdrawing from the community. 14,23 This is consistent with the research by Okoje et al 15 in Nigeria, in which as many as 6.4% of the respondents surveyed felt depressed over the loss of teeth. Feelings of regret and limited the social activity were also displayed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It can reduce the level of confidence that leads to people withdrawing from the community. 14,23 This is consistent with the research by Okoje et al 15 in Nigeria, in which as many as 6.4% of the respondents surveyed felt depressed over the loss of teeth. Feelings of regret and limited the social activity were also displayed.…”
Section: Discussionsupporting
confidence: 84%
“…12 A research by Shah et al 14 showed that 58% of patients in India who lost all their teeth had difficulty in accepting the loss of teeth. Similarly, Okoje et al 15 showed that in the Nigerian society, the patients reported that the emotional effects caused by tooth loss are as follows: 12.9% felt sad, 6.4% were depressed, 14% felt loss of some major part of their body, 2.3% had a feeling of aging, and 7.6% of individuals felt they were not cared for. The results obtained from a study conducted on the people of India and Nigeria can be applicable to other people also, especially in the city of Banda Aceh.…”
Section: Introductionmentioning
confidence: 96%
“…The titles and, where necessary abstracts, were examined against the inclusion criteria and 1043 articles were further excluded under the criteria of exclusion mentioned earlier in the data extraction section, leaving a total of 16 studies. Following the assessment of these studies, eight studies were also excluded, since these were either related to the invalidated assessment tools to measure psychological distress related to tooth loss or failed to meet the selection criteria . Therefore, only eight texts were included in the current review; all of the included studies had a cross‐sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…Following the assessment of these studies, eight studies were also excluded, since these were either related to the invalidated assessment tools to measure psychological distress related to tooth loss [23][24][25][26][27] or failed to meet the selection criteria. [28][29][30] Therefore, only eight texts were included in the current review; all of the included studies had a cross-sectional design. The key characteristics of the included studies are reported in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Além disso, há um efeito negativo significativo no bem-estar e na qualidade de vida , Cunha-Cruz et al, 2007 que inclui dificuldade na fala e limitações na interação social, o que leva as pessoas a manterem a perda dentária como um segredo que não deve ser discutido (Okoje et. al., 2012)., Os indivíduos que tem dificuldade em aceitar a perda de um ou mais de seus dentes são menos propensos a aceitar a inevitável mudança no formato da face que ocorre em detrimento da perda dentária (Davis et al, 2000).…”
Section: Lista De Abreviaturas E Siglasunclassified